Mechanical Properties Of Concrete Mixed With Waste Glass - A.Emhemed Abushareb, Hamed, Dr. M. Solikin, M.T, Dr. Ir. Sri Sunarjono, M.T (2015)
The study of waste glass (WG) concrete mix was done to study mechanical properties of concrete mix with target characteristics strength 30MPa at 28 days age. The laboratory experimental study was conducted at Muhammadiyah University between October and December 2014,to find out the high strength and amount for Waste Glass as fine aggregates replacement in a concrete mix. Also alkali silica reaction (ASR) was determined by expansion test. For mechanical properties compressive strength, flexural strength and modulus of elasticity (MOE) were determined. All measurement was done in accordance to ASTM standard methods. Three sample content types of 10%, 15% and 20% concrete mix containing waste glass and control 0% concrete mix were prepared, casted and cured for 28 days before determination of mechanical properties, and mortar bar were caste and cured for 14 days for ASR determination. Results showed that highest measured characteristics strength was 30.72MPa, for flexural strength was 6.8MPa and for modulus of elasticity was 37.42MPa, and the high expansion test was 28% compared to control concrete mix. For the amount waste glass replacement was determined in relation to high characteristics strength yield which was found at 10% WG replacement. The conclusion reached to this study were; Maximum characteristic strength for glass concrete mix was reached with 10% fine aggregate replaced was 30.72Mpa at 28 days age. While for ASR ,fine aggregate replacement by waste glass showed expansion at all amount replaced.